A Case of Recurrent Hemorrhagic Corpus Luteum with Elevated Follicle-Stimulating Hormone, Controlled by Estrogen/Gestagen Therapy - Yoshihide Inayama; Koji Yamanoi; Baku Nakakita; Shimpei Shitanaka; Jumpei Ogura; Tsutomu Ohara; Mie Sakai; Haruka Suzuki; Koji Yasumoto; Ichiro Kishimoto; Yusuke Sagae; Yoshimi Kitawaki; et al. (Case Reports in Obstetrics and Gynecology)
A high secretion of follicle-stimulating hormone (FSH) in reproductive-aged women is unusual. We report a case of recurrent corpus luteum hemorrhage and subsequent ovarian torsion with markedly elevated FSH levels in a reproductive-aged woman in the absence of functional gonadotroph adenoma (FGA) or premature ovarian failure (POF). A 22-year-old nulligravid woman with a history of bilateral hemorrhagic corpus luteum and subsequent ovarian torsion presented with acute abdominal pain. An emergency salpingo-oophorectomy of the right side was performed, and the right ovarian torsion due to hemorrhagic corpus luteum was diagnosed. Laboratory tests revealed markedly elevated FSH levels (77.6 mIU/mL). FGA was suspected, but no evidence of tumor was identified. The left ovary enlarged again at one-month follow-up. Estrogen/gestagen therapy (EGT) was started, which reduced the enlarged ovary to normal size. Two years later, her pituitary hormonal status was evaluated in detail. Besides markedly elevated FSH level, slightly elevated LH (31.2 mIU/mL), normal total inhibin B (35.3 pg/ml), abnormally low anti-Müllerian hormone (AMH) (<0.03 ng/mL), and poor FSH response to gonadotropin-releasing hormone stimulation test were found. In the absence of FGA, we conclude that certain disorders of inhibitory factors for FSH function, including inhibin and AMH may exist, which could attribute to the patient’s symptoms. EGT was very effective in suppressing the ovarian hyperactivity.